Low-frequency vibration measurement by temporal analysis of projected fringe patterns - Fu, Yu (2011)
Fringe projection is a whole field, non-contacting optical technique allowing direct measurement of surface contour of an object. In many cases, 3D surface profiling is required for vibrating objects or for objects with continuously changing profile, where conventional phase shifting techniques are not applicable. Carrier-based spatial Fourier, window Fourier analyses, or wavelet analysis are normally used to retrieve instantaneous phase maps in dynamic measurement from one fringe pattern, but these techniques require high-quality surface, such as uniform reflectivity, continuity of the surface and a regular shape. Otherwise, large errors will be generated during the process. In this study, a grating is projected on the surface of a low-frequency vibrating object and a sequence of fringe patterns is captured by a high-speed camera. The fringe patterns are processed point-by-point along time axis by different algorithms. To avoid the phase ambiguity problem, a temporal carrier is introduced in the experiment by shifting the grating with a constant speed. The results show that high-quality instantaneous surface profile and the kinematic parameters of vibration, such as displacement, velocity and acceleration can be obtained precisely.